The Application of Learning Model Type Jigsaw To Improve the Learning Outcomes of IPS Students In Class VII MTs Negeri 2 Rantau Prapat - Dema Yulianto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This study aims to : (1) To determine the level of learning outcomes of IPS students by using learning model Type Jigsaw. (2) To improve the learning outcomes of IPS students of MTs Negeri 2 Rantau Prapat that learned using the learning model Type Jigsaw (3) To determine the percentage increase in learning outcomes of IPS students after using the learning model Type Jigsaw. This research is a Classroom Action Research. The subject of this research is class VII MTs Negeri 2 Rantau Prapat Labuhanbatu city as many as 27 students. And the object of research is Through learning model Type Jigsaw in improving student social studies learning outcomes at MTs Negeri 2 Rantau Prapat . Based on the results of the initial test of the Value of student learning outcomes in classical before the applied learning model Type Jigsawa was of 18.5% with the criteria is very low. The value of learning outcomes of IPS students in the classical style after the applied learning model Type Jigsaw in the first cycle of 70,37%, mean value obtained by the students have not yet reached the classical completeness that is equal to > 85%.. This means an increase in learning outcomes of IPS students from before the action kesiklus I of 51,85%, and from cycle I to cycle II by 22,22%. From this study resulted in the conclusion that the learning model Type Jigsaw can improve learning outcomes of students of class VII MTs Negeri 2 Rantau Prapat.